PENERAPAAN PENDIDIKAN KARAKTER MELALUI PENGEMBANGAN DIRI PESERTA DIDIK - Firmansyah Firmansyah; Ayu Astari Iksan (Kelola: Journal of Islamic Education Management, 2021)
This study aims to determine the application of character education through self-development which was carried out in Madrasah Ibtidaiyah DDI 1 Palopo, the policies of the leadership of Madrasah Ibtidaiyah DDI 1 in the application of character education and what factors were supporting and inhibiting the application of character education through self-development in Madrasah Ibtidaiyah DDI. 1 Palopo. This research is included in the category of qualitative research with a phenomenological approach. The results showed that the application of character education at Madrasah Ibtidaiyah DDI 1 Palopo was integrated into learning by taking into account three aspects, namely teaching, exemplary, and evaluation. The madrasa principal's policy in implementing character education at Madrasah Ibtidaiyah DDI 1 Palopo is carried out by working meetings (Raker) with the board of educators in instilling character values in students. As well as the supporting and inhibiting factors in the application of character education through self-development of students at Madrasah Ibtidaiyah DDI 1 Palopo.